Environment, Nationalism and Sustainability: Racial minorities of Ganges Delta - K. Vedi, Puranjay (European Journal of Sustainable Development, 2017)
Ganges Delta region of South Asia fosters a harmonious construct of deceptively similar primordial identity markers shared by the people of India and Bangladesh. The unique cultural syncretism is a product of common history shared by the two. 1947 partition of India led to territorial demarcation broadly on religious lines and created West-Pakistan (Present day Pakistan) and East-Pakistan (Present day Bangladesh). In 1971 people of East Pakistan re-affirmed their allegiance to Bengali culture, language and intelligentsia and became independent nation. However Environmental calamities such as high tides, storm surges, rise in sea level altogether hampered Bangladesh’s growth. Bangladeshi migrants in search of better prospects, and taking advantage of deceptively similar identity markers and porous borders, entered India. This led to Assam Movement of 1971 voicing apprehension of Assamese that gradual alteration of demographic complexion of State of Assam and rise in Bangladeshi settlers might severe Assam region from rest of India. Considering climate change induced migration, population growth and Nationalism in South Asia this paper seeks to devise sustainable government policies which transcend precincts of national territories and appreciate need of present generation without jeopardizing interest of future generation. Keywords: Climate change, National Identity, Illegal Migration, sustainable government policy